Effects of an intergenerational program on adolescent self‐concept clarity: A pilot study. Issue 3 (18th October 2021) - Thomas, Nicole Maria; Hofer, Jan; Kranz, Dirk
Abstract: Objective: This pilot study examined the effects of a newly developed intergenerational program on self‐concept clarity (SCC) of adolescent participants. Method: In 12 encounter groups, 58 secondary school students and 50 nursing home residents shared their life stories and discussed existential questions about life (e.g., important values in life, how to deal with failure and regret). The life story encounter program (LSEP) is based on the dyadic Life Story Interview and was expanded into a group format consisting of ten 90‐min sessions. SCC was measured with the SCC Scale before, shortly after, and three months after the end of the LSEP. Results: Analyses suggest that adolescent LSEP participants' SCC improved compared to a control group (no LSEP participation). Findings also indicate that increases in SCC were associated with LSEP participants' extraversion and agreeableness. Conclusions: The LSEP is a promising program for fostering SCC in adolescence. Implications for the application of the LSEP are discussed.